Inhaled ciclesonide in adults hospitalised with COVID-19: a randomised controlled open-label trial (HALT COVID-19) - Peter Ueda; Johan Hansson; Johan Ljungberg; Anders Krifors; Björn Johansson; Martin Larsson; Per Tornhammar; Daniel Peter Andersson; Daniel Brodin; Eli Westerlund; Simon Athlin; Sandra Wojt; et al. (BMJ Open)
Objective To assess the efficacy of inhaled ciclesonide in reducing the duration of oxygen therapy (an indicator of time to clinical improvement) among adults hospitalised with COVID-19.Design Multicentre, randomised, controlled, open-label trial.Setting 9 hospitals (3 academic hospitals and 6 non-academic hospitals) in Sweden between 1 June 2020 and 17 May 2021.Participants Adults hospitalised with COVID-19 and receiving oxygen therapy.Intervention Inhaled ciclesonide 320 µg two times a day for 14 days versus standard care.Main outcome measures Primary outcome was duration of oxygen therapy, an indicator of time to clinical improvement. Key secondary outcome was a composite of invasive mechanical ventilation/death.Results Data from 98 participants were analysed (48 receiving ciclesonide and 50 receiving standard care; median (IQR) age, 59.5 (49–67) years; 67 (68%) men). Median (IQR) duration of oxygen therapy was 5.5 (3–9) days in the ciclesonide group and 4 (2–7) days in the standard care group (HR for termination of oxygen therapy 0.73 (95% CI 0.47 to 1.11), with the upper 95% CI being compatible with a 10% relative reduction in oxygen therapy duration, corresponding to a <1 day absolute reduction in a post-hoc calculation). Three participants in each group died/received invasive mechanical ventilation (HR 0.90 (95% CI 0.15 to 5.32)). The trial was discontinued early due to slow enrolment.Conclusions In patients hospitalised with COVID-19 receiving oxygen therapy, this trial ruled out, with 0.95 confidence, a treatment effect of ciclesonide corresponding to more than a 1 day reduction in duration of oxygen therapy. Ciclesonide is unlikely to improve this outcome meaningfully.Trial registration number NCT04381364.